Labor absorption with import substituting industrialization: An examination of elasticities of substitution in the Brazilian manufacturing sector - William G. Tyler (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1972)
In the less developed countries employment generation has emerged as a major problem. Those countries characterized by import substituting industrialization have been especially unable to expand employment opportunities, and their industrialization has been capital intensive in nature. Two different explanations for the failure of import substituting industrialization to absorb labor have been put forth. One school of thought Stresses the structural characteristics of industrialization, while an alternative explanation focuses on distortions in the factor markets. Much of this controversy implicitly revolves around the magnitude of the elasticities of Substitution — the "structural critic" school maintaining very Iow, or zero, elasticities of Substitution and the "market critic" school implying relatively high elasticities of Substitution. The CES production function is fitted to a regional cross-section of twenty-two Brazilian industries. The OLS estimates, made from 1960 industrial census data, show elasticities of Substitution ranging from .44 to 2.67 with over 50 percent of those estimated falling between .8 and 1.1. For the total manufacturing sector the elasticity of Substitution (estimated across states) was 1.0. The relatively high estimated elasticities of Substitution provide Support for the "market critic" school. Using the production function estimates to generate factor demand functions, the importance of factor market distortions is indicated. Distortions in the Brazilian labor market are quantified and, assuming their removal, a Iower bound estimate of the resulting employment generation is made, amounting to an increase of 11.4 percent in total manufacturing employment. Because of data limitations and the difficulties in quantification, no similar estimates were made regarding the capital market distortions.
Keywords: 330